Produção e caracterização de biochar de palha de cana-de-açúcar (Saccharum sp.) - Pires, Isis Cristina de Souza Adhmann (Universidade Federal de São Carlos, 2017)
The aim of this work was to study pyrolysis conditions (thermal degradation in a controlled presence of oxygen) for make biochar is a kind the raw-material used was the sugarcane straw (Saccharum sp.), that is an abundant residue in the fields. Pyrolysis techniques were used with fixed time of 3 hours and temperature variations of 200 °C, 250 °C, 300 ° and 400 °C, totalizing four treatments. The Biochar produced was characterized by immediate and thermogravimetric analyses. The obtained results showed the lignocellulosic materials transformation to fixed carbon, and the direct influence of pyrolysis temperature on cellulose and lignin degradation. The fixed carbon content obtained for the treatments carried out were T1 = 42 %, T2 = 51 %, T3 = 59 % and T4 = 65 %. The gravimetric yields were T1 = 55 %, T2 = 36 %, T3 = 30 % and T4 = 25 %. It can be observed the direct influence of the pyrolysis temperature in the cellulose and lignin degradation in the thermogravimetric analyses. Aiming the equilibrium between gravimetric yield and fixed carbon content, can be concluded that the better temperature for the slow pyrolysis, in the conditions developed in this work, was about to 250 °C.
Production and characterization of sugarcane straw biochar (Saccharum sp.)
Keywords: Biomassa; Biomass; Pirólise; Carbono fixo; Pyrolysis; Fixed carbon; CIENCIAS EXATAS E DA TERRA